A KINETIC STUDY OF THE DECOMPOSITION OF PYRIDINE CHROMIUM (VI) PEROXIDE WITH ALCOHOLS (Journal of Sciences, Islamic Republic of Iran)
A kinetic study of the decomposition of pyridine chromium peroxide with methanol, ethanol, propanol and isopropanol has been made over the temperature range 25 to 40°C. It is found that the ligand exchange stage is the rate determining step in the oxidation process. The activation parameters E , ?H‡ and ?S‡ for the reactions are determined. It is believed that the peroxide linkage is primarily responseble for the oxidation process